The Happiness and personal satisfaction on work. Statistical analysis of venezuelan merchant marine officer (2021) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
The purpose of this article is to assess at a given time the degree of happiness and satisfaction as well as the factors that may have a contrary effect from the perspective of 43 officers of the Venezuelan merchant marine based on their professional career as 1st officers from the work environment deriving from this their family and personal relationship. The research methodology used is descriptive in nature, considering that the degree of depth with which the object of study was addressed consisted of characterizing the phenomenon of temporality and the work environment. In relation to the design, the research is based on the collection and analysis of data through the application of a survey that included variables such as salary compensation, professional development, balance between work and personal life and recognition obtained, among others. In this sense, it is foreseen in the prospective longitudinal design to maintain and expand, if necessary, the variables studied over a certain period in order to observe the evolution in the population object of this study, scheduled every 02 years to follow up on the original group and make adjustments if necessary to the object of study to incorporate interviews and medical evaluations.
Keywords: happiness; satisfaction; analysis